Perbandingan Formulasi dan Uji Aktivitas Sun Protection Factor (SPF) Sediaan Lotion dari Berbagai Ekstrak Daun secara Spektrofotometri: Literatur Review - Elina Jatindria; Intan Nova Kaesa; Mutiara Eka Putri; Selvi Iswandari; Aldo Octavian Ramadhan Saputra (Lembaga Pengembangan Kinerja Dosen, 2026)
This systematic literature review aims to evaluate the formulation characteristics and Sun Protection Factor (SPF) activity of lotions containing various plant leaf extracts, which were tested in vitro using UV-Vis spectrophotometry. Exposure to ultraviolet (UV) radiation can cause various skin disorders, such as redness, premature aging, and an increased risk of skin cancer. With the growing interest in natural cosmetics, plant extracts containing flavonoids, phenolics, and tannins are increasingly being developed as active ingredients in natural sunscreens. Used in the final formulation. The study results indicate that leaf extracts from several plants, such as Nephelium lappaceum, Muntingia calabura, Crassocephalum crepidioides, and Carica papaya, possess UV-absorbing capabilities that are influenced by the extract concentration in the formulation. The most commonly used lotion formulation is an oil-in-water (O/W) emulsion with a combination of emulsifiers such as stearic acid and triethanolamine, which play a role in maintaining the physical stability, pH, viscosity, spreadability, and homogeneity of the preparation. The resulting SPF values vary, with the highest value approaching 30 in the 10% rambutan leaf (Nephelium lappaceum) extract lotion, placing it in the ultra-protection category. The UV-protective activity of the leaf extract is believed to be related to its polyphenol content, which can absorb UV radiation and help reduce sunburn. Based on the study results, the leaf extract-based lotion has the potential to be developed as a natural sunscreen. However, further research is still needed, particularly in vivo testing, irritation testing, photostability testing, and long-term stability testing to ensure the safety, efficacy, and stability of the formulation.